(untitled) (Bangladesh Journal of Pharmacology, 2016)
The main purpose of the current study was to study the antitumor effects of iridomyrmecin against human cervical cancer cells (HeLa). Its effects on apoptosis induction, cell cycle phase distribution, PI3K/Akt signalling pathway and long non-coding RNA (lncRNA) were also investigated. Cytotoxic effects of iridomyrmecin were evaluated by MTT assay while the apoptotic effect was assessed by flow cytometry using annexin V-FITC assay. Western blot assay was used to study effects on PI3K/Akt signalling pathway. Results exhibited that iridomyrmecin led to concentration-dependent as well as time-dependent growth inhibitory effects. Iridomyrmecin-treated cells showed signs of early and late apoptosis. Iridomyrmecin treatment also led to sub-G1 cell cycle arrest as well as induced loss of mitochondrial membrane potential (??m). Further, Western blot assay revealed that iridomyrmecin treatment resulted in down-regulation of PI3K/Akt protein expressions in a dose-dependent manner while as it up-regulated lncRNA CCAT2 expression. Video Clip of Methodology: Flow cytometry for cell cycle analysis: 3 min 20 sec Full Screen Alternative